Resilience And Parenting Stress For Mothers Who Have Children With Autism Disorder During The COVID-19 Pandemic In Indonesia - Indriasari, Fika Nur; Kusuma, Prima Daniyati (Universitas Muhammadiyah Semarang, 2024)
The COVID-19 pandemic has created a risk in families, especially for those with children with special needs. An inappropriate response to the impact of the pandemic has the potential to make the existing condition worse. The implementation of social restrictions causes all activities to be carried out at home, both working and studying. The positive thing is that parents have more time to take care of their children. However, there are also parents who complain of fatigue and find it difficult, especially those who have children with special needs such as autism. The closure of treatment centers such as speech therapy and physical and social skills has an impact on the development of their basic skills. This is a challenge for parents in raising them in the current situation. The aim of this study was to understand the influence of resilience towards parenting stress on mothers of children with autism disorder in the COVID-19 pandemic. The research design used was cross-sectional. The population in this study were mothers of a child with autism disorder who attended the Pembina Special School in Yogyakarta, Indonesia. The sampling technique used was total sampling. Linear regression analysis was used in the study. The study result showed p-value 0.023 < 0.05, which means that there is an influence on the level of resilience with parenting stress experienced by mothers who have children with autism disorder during the COVID-19 pandemic. The resilience level of mothers was at a moderate level, although mothers’ parenting stress was low. Parenting guidance and assistance for children with autism disorder needs to be done. This aims to improve coping strategies and family resilience during the COVID-19 pandemic.